Representasi Perempuan dalam Pariwisata di Pantai Toronipa Desa Toronipa Kecamatan Soropia Kabupaten Konawe Sulawesi Tenggara - La Ode Sudu; Lestariwati Lestariwati; Nurmin Suryati; Salebaran Salebaran; Taufiq Said (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2024)
Gender inequality can often hinder the development of tourism, especially in Toronipa Beach, Konawe Regency, Southeast Sulawesi Province. The objective of research is to be an alternative to reduce gender inequality in tourism development that has not been intended to women. The theory used in this research is tourism theory with ethnographic method proposed by Spradley (2006) that the analysis of women's representation must be in accordance with field data. The results shows that women's participation in tourism activities at Toronipa Beach has several impacts: positive impacts including land utilization, increasing income, and making business run more easily, and negative impacts including less time for children, and competition between traders, and social conflict. The representation of women in tourism activities is expected to increase the vocabularies of tourism science.